4(9x-9)=49x-4

Simple and best practice solution for 4(9x-9)=49x-4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(9x-9)=49x-4 equation:


Simplifying
4(9x + -9) = 49x + -4

Reorder the terms:
4(-9 + 9x) = 49x + -4
(-9 * 4 + 9x * 4) = 49x + -4
(-36 + 36x) = 49x + -4

Reorder the terms:
-36 + 36x = -4 + 49x

Solving
-36 + 36x = -4 + 49x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-49x' to each side of the equation.
-36 + 36x + -49x = -4 + 49x + -49x

Combine like terms: 36x + -49x = -13x
-36 + -13x = -4 + 49x + -49x

Combine like terms: 49x + -49x = 0
-36 + -13x = -4 + 0
-36 + -13x = -4

Add '36' to each side of the equation.
-36 + 36 + -13x = -4 + 36

Combine like terms: -36 + 36 = 0
0 + -13x = -4 + 36
-13x = -4 + 36

Combine like terms: -4 + 36 = 32
-13x = 32

Divide each side by '-13'.
x = -2.461538462

Simplifying
x = -2.461538462

See similar equations:

| -1.8(z-18)=-1.8(z-1.5) | | (1-x)(0.2-x)=0 | | 3xy-6x=6 | | 55=.2(2.85-10e) | | 4x^2(1-x^2)-1=0 | | (3a)*(5b)= | | 6*(x+5)=51 | | 24x+7=5+5x | | cox(x)+cos(5x)=1 | | (n-0)(n-1)(n-2)(n-3)(n-4)=0 | | (3a)x(5b)= | | 6*(x+5)=90 | | [23/12]1.2= | | 5(2x+6)=31 | | 0.6x=5 | | 7x^2-6x-162=0 | | 11y^2-45y-36=0 | | 14+15-18x+41x=19-12-23x | | (x+1)*(x+6)= | | 7-(1)/(x) | | 6(2x-3)=43 | | 5(x-5)=17 | | 8q(2q+8)= | | 3b-11=4 | | 7g(-3g-6)= | | 26-2v=5v+5 | | -3(6x-4y^2)= | | (9x-5)(x+1)=4x | | s=.2(65-40) | | 15y-4=24 | | 3x+0.3y=2.4 | | 6p(3+9p)= |

Equations solver categories